The Integration of Blockchain Technology in the Digital Economy: Ensuring Security and Transparency in Digital Transactions - Dong, Charles (Transactions on Economics, Business and Management Research, 2024)
This paper delves into the integration of blockchain technology within the digital economy, emphasizing its transformative potential to significantly enhance security and transparency in digital transactions. The digital economy, characterized by the rapid growth of online markets, digital banking, and e-commerce, has fundamentally altered how businesses operate and how consumers engage with products and services. However, this rapid digitization has also introduced a range of challenges, particularly concerning the security and transparency of online activities. Issues such as cybersecurity threats, fraud, data breaches, and the opacity of certain systems have underscored the need for more robust mechanisms to protect digital transactions. Blockchain technology, initially developed to underpin Bitcoin, presents a promising solution to these challenges. By offering a decentralized, immutable ledger system, blockchain has the inherent capability to enhance the security and transparency of digital transactions across various sectors. This study not only explores Satoshi Nakamoto’s foundational contributions to blockchain technology but also examines the broader implications and advancements proposed by Don and Alex Tapscott. Furthermore, it investigates the potential applications of blockchain across multiple industries, including finance, supply chain management, and corporate governance, to create more secure, transparent, and efficient systems.